2012
DOI: 10.1371/journal.pone.0040596
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Membrane GRP78 in Trophoblastic Cell Fusion

Abstract: BackgroundGlucose-regulated protein 78 (GRP78) is highly expressed in first trimester cytrophoblastic cells (CTBs), especially in syncytiotrophoblast (STB). However, the role of GRP78 in these cells has never been investigated.Methodology/Principal FindingsIn this study, we have examined the role of GRP78 in trophoblast fusion using the Bewo choriocarcinoma cell line as a model of cytotrophoblast fusion. Down regulation of GRP78 by siRNA or chemical inhibitors and use of antibodies against GRP78 in culture med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Based on the HCQ concentration used in the literature and its effects on BeWo cell viability (Figure S1), we decided to treat cells at 0.5 μg mL −1 HCQ for 48 h. At this concentration, HCQ completely reversed the effect of the APS patient's plasma (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the HCQ concentration used in the literature and its effects on BeWo cell viability (Figure S1), we decided to treat cells at 0.5 μg mL −1 HCQ for 48 h. At this concentration, HCQ completely reversed the effect of the APS patient's plasma (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…BeWo cells fuse in response to FSK-induced cAMP level and have been extensively employed as an in vitro model for studying various placental trophoblast functions (Wice et al, 1990;Fradet et al, 2012). KLF6 protein was already expressed in untreated cells (0 h) and was rapidly up-regulated by FSK treatment after 2 h, decreasing near to basal levels after 48 h (Fig.…”
Section: Klf6 Is Expressed In Bewo Cells and Its Down-regulation Redumentioning
confidence: 99%
“…The hypoxic conditions, which are known to exist in the tumor environment, are capable of eliciting the UPR. Interestingly, we have shown that GRP78, master regulator of the UPR, is involved in physiological cell fusion leading to formation of syncytiotrophoblast [22]. In order to test the UPR involvement in ovarian cancer cell fusion, we treated SKOV3 and COV318 cells with ERS inducers.…”
Section: -Ers Increases Cancer Cell Fusionmentioning
confidence: 99%
“…In ovarian cancer cells, GRP78 was shown to be overexpressed [21], suggesting UPR activation in these cells. Interestingly, GRP78 plays also an important role in trophoblastic cell fusion [22,23]. We thus hypothesized that UPR activation could be involved as well in EOC cell fusion and hence the occurrence of PGCCs.In this article, we confirmed Zhang et al results stating that PGCCs derive at least partially from cell fusion in SKOV3 cells [9].…”
mentioning
confidence: 99%